Assessment of the Distribution and Accumulation of Polybrominated Diphenyl Ethers in the Environment in the Plastic Recycling Village of Minh Khai, Nhu Quynh Town, Hung Yen Province - Tham, Trinh Thi; Huong, Nguyen Thi; Phuong, Bui Thi; Trinh, Le Thi (VNU Journal of Science: Earth and Environmental Sciences, 2018)
This study assessed the accumulation of 07 polybrominated diphenyl ether (PBDEs) indicator congeners (BDE-28, BDE-47, BDE-100, BDE-99, BDE-154, BDE-153, BDE-183) in sediment, in tissue of the Anodonta cygnea and Pomacea canaliculata in the Minh Khai Plastic Recycling Village, Hung Yen Province. Samples were extracted by Soxhlet Extraction and quantified on GC/MS using internal standard calibration. The concentration of total PBDEs in the sediments and biota samples ranged from 6.03 to 183 ng/g in dry wt and 10.2 to 129 ng/g in wet wt, in respectively. The results showed that the accumulation of PBDEs in sludge sediments in this areas was rather high, and there was a positive correlation between PBDEs content in biological samples and sediment samples. The high values of BSAF demonstrated the high bioaccumulation potential of PBDEs in biota. This is the scientific basis for the assessment of ecological and environmental risks of PBDEs pollution in the village environment. Keywords: PBDEs, BSAF, sediment, accumulation.